Pigmentary mosaicism and extracutaneous defects: a case report of a rare form of twin spotting - Mohamed H.M El-Komy; Eman A EL-Nabarawy; Heba A Abdelkader; Mona R.E Abdel-Halim; Randa S EL-Aguizy (Wolters Kluwer Medknow Publications, 2021)
Progressive cribriform and zosteriform hyperpigmentation (PCZH) is an uncommon disorder of pigmentation that is believed to be a result of pigmentary mosaicism. In this report, we describe a child with congenital nevus depigmentosus and low intelligence who later developed PCZH by the age of 5 years.